UPAYA MENINGKATKAN KEMAMPUAN MENULIS KARANGAN MELALUI METODE IMAGE STREAMING DENGAN MEDIA GAMBAR SERI - Marhatillah Marhatillah; Nora Akmalia (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2017)
This study aims to find out how the effort to improve the students’ writing skill through image streaming method using the image series media on Indonesian Language in Fifth Grade at SD Negeri Paya Peunaga Meureubo Subdistrict. The research approach used qualitative approach with Classroom Action Research type (PTK), which consists of pre action and two cycles in which there are four stages: planning, implementation, observation and reflection. The subject of this research were all fifth grade students of SD Negeri Paya Peunaga Meureubo District, West Aceh District, which amounted to twenty eight students. Data collection techniques used observation, test, documentation and validation. Instruments in this study are observation sheet, test sheet and validation sheet. Data analysis technique used percentage descriptive. Based on the result of this research at the pre-action stage, only eight students or 28,6% students who complete with the average value of the overall student is 57,14. In the first cycle, there are seventy students or 60,7% who complete with the average value of the overall student is 65,2. In the second cycle, twenty three students or 82,1% have reached mastery with the average score of students is 72,8. The result of observation on teacher activity in the first cycle is 72,9% including in good category whereas in the second cycle reach 85,4% in very good category. The result of observation in the first cycle is 68,2% including enough category, while in the second cycle reach 79,5% in good category. Thus the use of image streaming with image series media in Indonesian Language learning can improve the writing ability of the fifth grade students of SD Negeri Paya Peunaga.